Enhancing Gross Motor Skills in 5-6 Year Old Children Through Graded Zone Throwing and Catching Ball Play: A Classroom Action Research Study - Muntaha, Sindi Tafrihatul; Rochimah, Nur; Nirmala, Ine (Transformasi : Jurnal Penelitian dan Pengembangan Pendidikan Non Formal Informal, 2026)
Gross motor competence in early childhood supports participation in active play and provides a foundation for later movement, health, and learning experiences. This study examined whether graded-zone throwing-and-catching ball play could improve gross motor performance among children aged 5–6 years in an Islamic early childhood education setting in Karawang, Indonesia. A collaborative classroom action research design was implemented with 13 children (7 girls and 6 boys) through a pre-action assessment and two iterative cycles. Cycle I comprised six meetings, whereas Cycle II comprised four meetings refined on the basis of classroom reflection. The intervention progressed from an easy zone, emphasizing short-distance throws, slow catches, stable posture, and direct modelling, to a challenge zone involving greater distance, faster responses, movement, targets, and simple obstacle courses. Gross motor performance was observed across body coordination, strength, balance, and agility using a four-level developmental rubric. Sixteen retained instrument items demonstrated a Cronbach’s alpha of 0.857. The class mean increased from 40.27% at pre-action to 50.96% in Cycle I and 77.94% in Cycle II, exceeding the predetermined 75% classroom success criterion. Final domain means were 80.41% for coordination, 76.44% for strength, 76.08% for balance, and 78.85% for agility. Qualitative observations also indicated more stable posture, faster responses, improved movement sequencing, and greater confidence during ball tasks. The findings suggest that progressively structured, low-cost throwing-and-catching play is a promising classroom strategy for gross motor development, while the single-class action-research design limits causal and population-level inference.